BUREAUCRATIC REFORM THROUGH INTEGRATED ADMINISTRATIVE SERVICES IN BETOAMBARI DISTRICT, BAUBAU CITY - Afi, Mohammad Fajr; Achamar, Farid Yusuf Noor; Ghazalin, Junaid (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2024)
In order to enhance public services, it is important to revamp the administration of such services. The initial step towards accelerating administrative reform is to achieve good governance, which prioritizes enhancing the quality of public service provision. With the advent of Reformasi, the Regional Government now has the chance to maximize the function of the sub-district in order to enhance access and improve the quality of services through the Integrated Administrative Service Program of the sub-district. The objective of this research is to investigate the impact of implementing integrated administrative services on bureaucratic reform in Betoambari District, Baubau City. This study employs a descriptive research method with a qualitative approach. The study's findings indicate that the implementation of the District Administration Integrated Service Program has successfully improved the quality of services in Betoambari District. Specifically, the Public Service Administration Reform has streamlined and simplified administrative processes, making them more accessible to the community. Regarding service quality dimensions, Betoambari sub-district demonstrates commendable performance in almost all areas. However, there is still room for improvement in order to enhance the effectiveness, efficiency, and accessibility of services for the community.